ICTV Virus Taxonomy Profile: Hypoviridae - Suzuki, Nobuhiro; Ghabrial, Said A.; Kim, Kook-Hyung; Pearson, Michael; Marzano, Shin-Yi L.; Yaegashi, Hajime; Xie, Jiatao; Guo, Lihua; Kondo, Hideki; Koloniuk, Igor; Hillman, Bradley I. (Journal of general virology, 2018)
The Hypoviridae , comprising one genus, Hypovirus , is a family of capsidless viruses with positive-sense, ssRNA genomes of 9.1–12.7 kb that possess either a single large ORF or two ORFs. The ORFs appear to be translated from genomic RNA by non-canonical mechanisms, i.e. internal ribosome entry site-mediated and stop/restart translation. Hypoviruses have been detected in ascomycetous or basidiomycetous filamentous fungi, and are considered to be replicated in host Golgi-derived, lipid vesicles that contain their dsRNA as a replicative form. Some hypoviruses induce hypovirulence to host fungi, while others do not. This is a summary of the current ICTV report on the taxonomy of the Hypoviridae , which is available at www.ictv.global/report/hypoviridae .